“Germany and World”: Dmitry Merezhkovsky interviewed by the French journalist Marylie Markovitch - Alexander Stroev (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article is dedicated to the interview which Marylie Markovitch (1866 – 1926, born Amelie Neri), the French journalist and writer of the feminist trend, had with Dmitry Merezhkovsky. The meeting took place in the fall of 1915 during Markovitch’s stay in Russia as a special correspondent for “Le Petit journal” and “Revue des Deux Mondes”, however, unlike other Markovitch’s publications, the interview with Merezhkovsky was published behind time, on January 22, 1916. The author notes that both the writer and the journalist address directly to censorship, with Markovitch managing, however, to convey the position of the Russian liberal intelligentsia to the French reader. According to the author of the article, Markovitch represents Merezhkovsky not only as a famous author, well known in France, but as a prophet, quoting his article “Iron under the Hammer” in the first part of the interview. The original French text of the interview, accompanied with the Russian translation, is fully reproduced in the article. The publisher’s attention is focused on an attempt to reconstruct the subtext of the interview, which is profoundly affected by Markovich and Merezhkovsky’s conscious striving for a theatricalized dialogue.